incorporación en el Régimen de Alimentos, la solicitud de rendición de cuentas de la Pensión Alimenticia - Yaguana Olmedo, Christian Fernando (2018)
This thesis aims to legal arguments on the use of maintenance and breach of the rights guaranteed in the constitution and regulations of the Code of Children and Adolescents in the part of the food, and make a connection with the Codes of Childhood and Adolescence at international level; I have done extensive research of historical fact, in order to meet the early codes of Childhood and Adolescence and understand how it took place, I understand that maintenance payments are essential for sustaining itself as the needs generated by the obligor or instruction of minors who have been in need, for willful default of the mother, just as we make a deep study about alimony from the very meaning of rights, as well as food that is, the definition alimony. Which the answers of every question led to statistical analysis through the barcode to get the percentage of each question and to complete the total percentage of the five questions set out of Childhood and Adolescence in that note that the sample is consistent with the hypothesis was also obtained posed. Thus the policy under investigation in this tube substantial generated by the obligor or instruction of minors family visits.